Utilização de enzimas xilanases para codornas de corte - Grecco, Erica Travaini (2016)
Three experiments were carried out to evaluate the effects of supplementation of two xylanase in diets based on corn and soybean meal for meat type quails on the metabolization of nutrients, performance, morphology of the intestinal mucosa and carcass yield. In the first experiment, 175 male meat type quails were allotted in a completely randomized design, distributed in a factorial arrangement 2x3 + 1 (two metabolizable energy reduction - 70 and 140 kcal/kg, and with or without addition of two xylanase - A and B, plus a control treatment without xylanase), with seven treatments and five replicates with five birds per replicate. There was interaction (P<0.10) between metabolizable energy reduction and inclusion of enzymes for metabolizability coefficients of crude protein, NDF and gross energy. The enzymes were effective in providing more nutrients for crude protein and NDF coefficients, and provided more energy for AMEn (P<0.10). In Experiment II 1575 meat type quails of one day age and non-sexed were allotted in a completely randomized design, distributed in a factorial arrangement 2x3 +1, with seven treatments and five replicates with 45 birds per replicate, submitted to treatments used in Experiment I. At 14 days of age jejunum segments were collected and morphometry was evaluated. There was no interaction (P>0.10) between metabolizable energy reduction and inclusion of enzymes for performance variables and jejune morphometry. Energy reductions only influenced feed intake. The reduction of 140 kcal/kg increased feed intake, while reduction of 70 kcal/kg decreased it, reflecting better average performance. For jejune morphometry, xylanases increased height of villi and villous:crypt. In Experiment III, 1490 meat type quails from 15 to 35 days of age were submitted to treatments used in Experiment II. At 35 days of age the carcass yield was evaluated and a jejunum segment was collected and evaluated intestinal morphometry. There was no interaction (P>0.10) between metabolizable energy reduction and inclusion of enzymes for performance variables, jejune morphometry and carcass yield. Energy reductions affect feed intake, weight gain and feed conversion, with best averages for energy reduction of 70 kcal/kg. For jejune morphometry, xylanases increase villus height and villus: crypt. It is concluded that xylanase is effective in energy reductions on corn and soybean meal diets for meat type quails from 1 to 35 days old.